2010
DOI: 10.1371/journal.pntd.0000913
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tropically Stable Oral Amphotericin B Formulation (iCo-010) Exhibits Efficacy against Visceral Leishmaniasis in a Murine Model

Abstract: PurposeTo develop an oral formulation of amphotericin B (AmB) that is stable at the temperatures of WHO Climatic Zones 3 and 4 (30–43°C) and to evaluate its efficacy in a murine model of visceral leishmaniasis (VL).MethodsThe stability testing of four novel oral lipid AmB formulations composed of mono- and di-glycerides and pegylated esters (iCo-010 to iCo-013) was performed over 60 d and analyzed by HPLC-UV. In addition, the four formulations were incubated 4 h in fasted-state simulated intestinal fluid. AmB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 7 publications
4
48
0
1
Order By: Relevance
“…Ranitidine, topotecan and amprenavir had the lowest predicted LogP (ALOGPS) at 0.79, 1.84, and 1.85, respectively. Amprenavir (72)(73)(74) C) [36] and ranitidine (69-70 C) have low melting points. Topotecan has a melting point of 213-218 C .Based on the above mentioned general rule, topotecan would be better formulated as an amorphous solid dispersion.…”
Section: Solubility Profiles Of Fda Approved Drugs In Lbddsmentioning
confidence: 99%
“…Ranitidine, topotecan and amprenavir had the lowest predicted LogP (ALOGPS) at 0.79, 1.84, and 1.85, respectively. Amprenavir (72)(73)(74) C) [36] and ranitidine (69-70 C) have low melting points. Topotecan has a melting point of 213-218 C .Based on the above mentioned general rule, topotecan would be better formulated as an amorphous solid dispersion.…”
Section: Solubility Profiles Of Fda Approved Drugs In Lbddsmentioning
confidence: 99%
“…By applying structural clustering and secondary assays to determine potency and selectivity, 70 compounds were identified that possessed 50% effective concentrations (EC 50 s) below 1 M and that did not inhibit the growth of mammalian epithelial cancer cells at this concentration. Given the need for a new small-molecule candidate for the oral treatment of leishmaniasis and our continuing efforts in this area (42)(43)(44), we decided to study selected members from the set of 70 antileishmanial molecules reported by Sharlow et al to determine whether any were candidates for further development as antileishmanial drug candidates. Several of the molecules that we evaluated displayed activity against intracellular Leishmania in vitro, and members of one class showed efficacy in a murine VL model.…”
mentioning
confidence: 99%
“…The formulation, named ICo-010, retained AmpB in simulated gastric and intestinal fluids and exhibited a significant antileishmanial activity in a VL-infected murine model. 75,76 ICo-010, currently being developed by iCo therapeutics, was granted orphan drug status by the FDA, but recent data from the company website do not show any further improvement from preclinical evaluations. 197 A NE loaded with doxorubicin (NE-DOX) was further grafted with phosphatidylserine (PS) to enhance the cellular uptake.…”
Section: Nanoemulsions (Nes) and Niosomesmentioning
confidence: 99%